Succession planning for community-engaged leaders: culture, context and continuity in equity-oriented leadership - White, Terrenda; Obregon, Monica; Resnick, Alison Fox; Farrell, Caitlin (Frontiers in Education, 2025)
Succession planning is typically rooted in linear models of transition informed by supply-and-demand rationales about the available pool of leaders to fill positions and the efficient transfer of information to new leaders. Equity-oriented leaders with commitments to community-engagement, however, represent different logics of expertise, which elevate knowledge of context and culture and enact collectivist and collaborative practices of leadership. This paper considers the adequacy of traditional succession planning for the continuity of leaders with non-traditional orientations to leadership. We build on an equity-centered model of succession planning–Dynamic Leadership Succession (DLS)–and connect it to key values of equity-oriented leadership: culture, context, advocacy, and collectivity. We consider practical implications for integrating equity-oriented leadership values with an equity-model of planning, posing new questions for system change and for district leaders interested in continuity of community-engaged leaders in diverse public schools.